2022
DOI: 10.3389/fmolb.2022.930207
|View full text |Cite
|
Sign up to set email alerts
|

Evolving role of seneca valley virus and its biomarker TEM8/ANTXR1 in cancer therapeutics

Abstract: Oncolytic viruses have made a significant inroad in cancer drug development. Numerous clinical trials are currently investigating oncolytic viruses both as single agents or in combination with various immunomodulators. Oncolytic viruses (OV) are an integral pillar of immuno-oncology and hold potential for not only delivering durable anti-tumor responses but also converting “cold” tumors to “hot” tumors. In this review we will discuss one such promising oncolytic virus called Seneca Valley Virus (SVV-001) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…SVV-001, an oncolytic picornavirus that occurs naturally, was initially discovered in 2002 in a cell culture that was likely contaminated with porcine trypsin or bovine serum contain- ing SVV-001. 32 SVV-001 has been proven to exhibit specific cytotoxicity towards tumor cells that exhibit neuroendocrine characteristics. 32 In this study, we sought to examine the impact of SVA on HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…SVV-001, an oncolytic picornavirus that occurs naturally, was initially discovered in 2002 in a cell culture that was likely contaminated with porcine trypsin or bovine serum contain- ing SVV-001. 32 SVV-001 has been proven to exhibit specific cytotoxicity towards tumor cells that exhibit neuroendocrine characteristics. 32 In this study, we sought to examine the impact of SVA on HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…SFV4miRT is the Semliki Forest Virus with inserted target sequences for miR124, miR125, and miR134 expressed more in normal CNS cells than in glioma cells [ 133 ]. Thus, this virus has reduced neurotropism with oncolytic efficacy and a safer profile [ 134 ]. Recently, studies have shown that the Zika virus (ZIKV) can infect the GB stem cells (GSCs) and have oncolytic activity on them [ 135 , 136 ].…”
Section: Oncolytic Viruses In Gbmentioning
confidence: 99%
“…This suggests that modifying ZIKV to more precisely target GB in the absence of normal neuronal cells may enhance treatment results [ 171 , 172 ]. ZIKV-LAV was created by a 10-nucleotide deletion in the 3′ untranslated region (3-UTR) of the genome.…”
Section: Novel Oncolytic Viral Therapy For Treatment Of Glioblastomamentioning
confidence: 99%